2020
DOI: 10.1186/s12544-020-0402-4
|View full text |Cite
|
Sign up to set email alerts
|

Mobility styles and car sharing use in Europe: attitudes, behaviours, motives and sustainability

Abstract: What are the profiles of both users and non-users of car sharing in European cities regarding their travel patterns and psychological aspects? Two subsamples (1519 users and 3695 non-users of car sharing) participated in a survey, translated into seven languages, with 36 questions regarding attitudes towards car sharing, the environment, political orientation, personal norms, frequency of use of different transport modes and transport mode choice for different travel purposes. Through a hierarchical cluster an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 65 publications
2
31
0
Order By: Relevance
“…According to Meijkamp [272], car-sharing members usually use more often other sustainable modes such as cycling and public transport. This analysis was recently confirmed by Ramos et al [273]; they observed that the majority of European car-sharing users have the weakest habits of private car use and prone to use sustainable transport modes.…”
supporting
confidence: 60%
“…According to Meijkamp [272], car-sharing members usually use more often other sustainable modes such as cycling and public transport. This analysis was recently confirmed by Ramos et al [273]; they observed that the majority of European car-sharing users have the weakest habits of private car use and prone to use sustainable transport modes.…”
supporting
confidence: 60%
“…More specifically, we postulate that the perception of ecological benefits is driving carsharing usage. While there is a growing interest in sustainable products and services (Atkinson and Rosenthal, 2014), environmental benefits have been identified as a nice add-on rather than a driver of carsharing usage (e.g., Lindloff et al, 2014;Hartl et al, 2018;Ramos et al, 2020). Our research offers new important insights into the role of perceived ecological perspective, even more dramatic figures are reported in the San Francisco Bay area for public transit: In November, the use of public transportation was 90% below the pre-pandemic level (Cohen, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…The Covid 19 pandemic also contributed to understanding smart cities' concept as a sustainable city model in 2020, which led to a change in urban mobilities. Cities started to accelerate the construction of pedestrians and cyclists' construction and prepare, together with private partners, a new car or bike-sharing concepts in cities [83]. The outbreak of COVID -19 in 2020 led to the closure of carsharing providers.…”
Section: Urban Sustainability and Car-sharingmentioning
confidence: 99%